Perancangan Konten Marketing Melalui Media Sosial Instagram Untuk Meningkatkan Tenant di Baros Information, Technology, & Creative Center Working Space Tahun 2024 - Khoirullah, Akfin; Cahyani, Leni (DINASTI RESEARCH, 2024)
: Co-working spaces have become a primary choice for professionals, freelancers, and startups seeking flexibility and collaboration opportunities. BITC Working Space, managed by UPT Cimahi Techno Park, is a co-working space in Cimahi City that provides various facilities to support tenants' businesses. This research aims to design, implement, and evaluate content marketing strategies through Instagram social media @bitc.workingspace to increase the number of tenants. The research uses a descriptive qualitative approach with data collection techniques including observation, interviews, documentation, and triangulation. Results show that content planning was carried out with relevant themes such as facility promotion, education, and motivation. Content marketing implementation was conducted through regular posts on both feed and story features. Evaluation showed an increase in engagement from 69 users in May 2024 to 459 users in July 2024, although it declined in the following month. The number of Instagram followers also increased from 95 to 113 during the research period. In conclusion, planned and consistent content marketing strategies proved effective in increasing brand awareness and audience interaction. This research recommends content optimization by maximizing Instagram features to support BITC Working Space's business objectives.